Hubungan Kompetensi Dengan Gaya Kepemimpinan Kepala Desa Di Kabupaten Kaur - Solichin Solichin (STIA Bengkulu, 2022)
Competence may be described as behaviors proven via way of means of the ones who've best overall performance, are extra steady and effective, in comparison to the ones who've a mean overall performance. Competence is a fundamental function of someone that permits him to offer advanced paintings in a specific job, role, or situation (Bakar, 2007). The competence that happens in Kaur district isn't owned via way of means of the village heads themselves, Kaur district has 192 villages. Lack of choice to be equipped and construct a village collectively in Kaur Regency which include the cappotential to steer and pay attention to network participation, nonetheless do now no longer recognize the guidance of plans, implementation of village sports each year. In the sector of education, the common village head is on the excessive college level, much less lively in collaborating in education events, much less capable of deal with situations while struggle happens, and frequently village heads do now no longer have self-guidance, so there may be no loss of motivation to excel. As a result, they're much less than gold standard in wearing out their principal responsibilities and capabilities because the village authorities management apparatus, which in truth does now no longer acquire overall performance goals, and is missing in figuring out the achievement of authorities, improvement and empowerment of rural communities.